Flexible higher education : international pioneers reflect - Burge, Elizabeth J. (Maidenhead : Open University Press, 2007)
Read this book to hear from 44 pioneers who helped drive key late 20th century changes in access to and learning in higher education, via distance education. The book reaches out to many post-secondary educators who want to think reflectively and beyond the box.
Includes bibliographical references and index.
1 2
Keywords: Open learning; Distance education; Education, Higher -- Aims and objectives; Education, Higher -- Effect of technological innovations on